THE ROLE OF LOCAL GOVERNMENT IN REALIZING SUSTAINABLE MARINE TOURISM IN PEMUTERAN VILLAGE GEROKGAK SUB DISTRICT BULELENG BALI PROVINCE - Ni Made Gandhi Sanjiwani (Institut Pariwisata dan Bisnis Internasional, 2019)
This paper aims to study the role of local government in realizing sustainable marine tourism. Pemuteran Village is one of the best practices of sustainable marine tourism in the developing world. Three types of government roles were studied, namely: regulator, facilitator, and of executor.. These roles were positioned as exogenous latent variables in a causal relationship with sustainable marine tourism in the village. Sustainability is measured through reflective constructs, i.e. economic benefit, socio-cultural benefit, and environmental benefit felt by the local community of Pemuteran Village. The data were collected from 60 respondents, consisting of community leaders, non-governmental organizations, and tourism industry stakeholders in Pemuteran Village. Then, questionnaires were analyzed by structural equation modelling—partial least square (path modelling). The results show that the government roles did not have a significant effect on marine tourism sustainability. However, the role of local government and the existence of marine tourism sustainability were reflected significantly in its three constructs where the most represented construct in this relationship respectively are the role of facilitator and the environmental benefit. The most important finding in this research is that the role of local government was not only measured by regulator and facilitator roles, as in previous research, but includes analysis of the executor role. which proved significant in structural model evaluationone of the best practices of sustainable marine tourism — – partial least square (path modelling). The results show that the government roles did not have aprove significantly aeffect on marine tourism sustainability. However, the role of local government and the existence of marine tourism sustainability were reflected significantly in its three constructs where the most represented construct in this relationship respectively are the role of facilitator and the environmental benefit. The most important finding in this research is that the role of local government waswere not only measured throughtby regulator and facilitator roles, as inthe previous research did, but includes analysisalso of the by executor role. which is proved significantly in its structural model evaluation